2008
DOI: 10.1128/iai.00692-08
|View full text |Cite
|
Sign up to set email alerts
|

Type IV Pili and the CcpA Protein Are Needed for Maximal Biofilm Formation by the Gram-Positive Anaerobic Pathogen Clostridium perfringens

Abstract: The predominant organizational state of bacteria in nature is biofilms. Biofilms have been shown to increase bacterial resistance to a variety of stresses. We demonstrate for the first time that the anaerobic gram-positive pathogen Clostridium perfringens forms biofilms. At the same concentration of glucose in the medium, optimal biofilm formation depended on a functional CcpA protein. While the ratio of biofilm to planktonic growth was higher in the wild type than in a ccpA mutant strain in middle to late sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 62 publications
6
110
0
2
Order By: Relevance
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
See 1 more Smart Citation
“…O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation. Since then, similar findings have been reported for a number of bacteria and archaea, including (but not limited to) V. cholerae, A. actinomycetemcomitans, Aeromonas caviae, Shewanella oneidensis, Legionella pneumophila, Caulobacter crescentus, Deinococcus geothermalis, C. perfringens, and Sulfolobus acidocaldarius (40,44,102,133,178,342,389,398,408,431).…”
Section: Biofilm Formation and Remodelingsupporting
confidence: 49%
“…All classes of T4P, and even the T2S hyperpseudopili produced upon overexpression of the major pseudopilin, can participate in biofilm development in a wide variety of bacterial and archaeal species by promoting initial (and often highly tenacious) adherence to surfaces, as well as cell-cell interactions (122,128,208,209,328,398,400). O'Toole and Kolter (304) first reported that P. aeruginosa mutants lacking T4P are deficient in biofilm formation.…”
Section: Biofilm Formation and Remodelingmentioning
confidence: 99%
“…Cell detachment might occur, which leads to the poor biofilm formation. In addition, many publications emphasized the importance of motility for the biofilm formation [21,22]. When cells were incubated with pyrite slices, large flat surfaces and reduced shearing forces provide a chance to facilitate their attachment on the surface.…”
Section: Biofilm Formation Of Sb Thermosulfidooxidans On Pyrite Undementioning
confidence: 99%
“…There is accumulating evidence that CcpA can also be involved in the control of virulence gene expression by several Gram-positive pathogens, including C. difficile and S. aureus (25)(26)(27)(28)(29). In C. perfringens, CcpA has been shown to control expression of the enterotoxin gene (cpe) and genes involved in type IV pilus formation and function (30,31). In addition to toxins, C. perfringens produces many enzymes, including three sialidases named NanJ, NanI, and NanH.…”
mentioning
confidence: 99%